Strategi Promosi Kesehatan Melalui Komunikasi Digital: Studi @Halodoc di Instagram - Azzahra, Dwi Vira; Aidha, Zuhrina; Fahzirah, Ranti; Silangit, Nurhidayah; Apriansyah, Bagus Halfin; Difhanny, Chairunnisyah Nurma; Aliyyah, Annisa Fijjannah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
To convey this, PT Media Dokter Investama created an official Instagram account named @halodoc so that messages can be conveyed quickly and thoroughly throughout Indonesia. Of course, PT Media Dokter Investama has a communication strategy in digital media that is right so that messages can be conveyed properly and certainly be responded to by the public or at least read by the general public on Instagram social media. The purpose of this research is to analyze health promotion through digital communication on @halodoc Instagram. Here, of course, PT Media Dokter Investama uses social media in the form of Instagram as new media to convey various information about health, tips and webinars about health. Of course, the thing that is taken into consideration is the height and the increasing number of Instagram users every year from Indonesia so that Instagram is considered effective for conveying this information. Apart from that, the market segment of dominant Instagram users is millennials and adults. This is of course related to the communication strategy conveyed by Instagram @halodoc because the information conveyed is quite scientific information and of course only understood by people who are growing up or adults. Keywords: communication strategy, Instagram, new media